2017
DOI: 10.1080/00365513.2017.1394488
|View full text |Cite
|
Sign up to set email alerts
|

Reference intervals for absolute and percentage immature platelet fraction using the Sysmex XN-10 automated haematology analyser in a UK population

Abstract: This large-scale study showed comparable reference intervals with the previous studies for %-IPF and A-IPF in a UK population. It found the need to establish sex-specific reference intervals for %-IPF, but not for A-IPF, whereas reference intervals were found to be stable across the age range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 52 publications
2
12
0
Order By: Relevance
“…The data for males and females were also treated as a single entity when considering the IPF%. The normal reference range established in the present study was 1.3-12.8%, which was in keeping with that derived by Ali et al (2017) [21]. However Ali et al did report on small but significant differences in IPF% between healthy males and females, and therefore derived two separate reference ranges.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The data for males and females were also treated as a single entity when considering the IPF%. The normal reference range established in the present study was 1.3-12.8%, which was in keeping with that derived by Ali et al (2017) [21]. However Ali et al did report on small but significant differences in IPF% between healthy males and females, and therefore derived two separate reference ranges.…”
Section: Resultssupporting
confidence: 92%
“…However Ali et al did report on small but significant differences in IPF% between healthy males and females, and therefore derived two separate reference ranges. The reason for the different findings between studies may simply be down to sample size, with the present study deriving the reference range from 171 controls, while Ali et al derived from a control population of 2366 [21].…”
Section: Resultsmentioning
confidence: 66%
“…Their results were consistent with an impact of smoking in a covariance model on platelet volume and IPF, 43 while Butkiewicz et al have found a significant higher percentage of reticulated platelet among smoking women compared to nonsmokers. 45,46 Platelet count was found slightly higher among smokers, even if that difference was not statistically significant, but immature platelet count was statistically significant higher in smokers. 45 In our study, conducted among patients undergoing coronary angiography, we found higher IPF among active smokers as compared to the nonactive ones, who were considered comparable to a "normal" control population, since comprising a heterogeneous and largely sized cohort of patients, including patients with and without CAD.…”
Section: Discussionmentioning
confidence: 74%
“…In fact, although we included also patients admitted for an acute coronary syndrome, the IPF% of our cohort was similar to the values those reported by other studies on European cohorts. 45,46 Platelet count was found slightly higher among smokers, even if that difference was not statistically significant, but immature platelet count was statistically significant higher in smokers. Moreover, smokers showed lower prevalence and diabetes, hypertension and renal failure and less pharmacological therapies.…”
Section: Discussionmentioning
confidence: 74%
“…The fluorescent dye is CD4K530 for Abbott analyzers and oxazine-based for Sysmex analyzers. Despite the poor standardization and a lack of correlation between the young platelet fraction measurements among the different instruments (absence of reference method and the existence of different reference ranges for different instruments), these parameters are good indicators of thrombopoietic activity [20][21][22]. IPF absolute count has been proven as an indicator of platelet recovery after chemotherapy in pediatrics [23] and, thus, has been proposed as a tool to categorize neonatal thrombocytopenia [24] or to predict peripheral immune thrombocytopenia [25,26].…”
Section: Fluorescence Platelet Countingmentioning
confidence: 99%